Hubungan Keberadaan Anggota Keluarga yang Merokok dan Status Gizi Balita dengan Kejadian ISPA - Baya, Nur (JIKI Jurnal Ilmiah Kesehatan IQRA, 2020)
Acute Respiratory Tract Infection (ARI) is a disease that is common in infants and children ranging from mild to severe ISPA. Objective to determine the relationship between the existence of family members who smoke and the nutritional status of children with the incidence of ispa in the working area of ​​the Padongko Kec Health Center. barru district. new year 2019. This research uses descriptive analytic design with cross sectional approach. The population is 31 mothers who face menopause. The sample in this study were 31 people. Total sampling technique, data collection with questionnaire. Data was processed using SPSS version 20 and univariate and bivariate analysis with chi-square statistical tests and presented in the form of a frequency distribution table. There is a relationship between the presence of family members who smoke and the incidence of ARI where p-value = 0.001 is obtained, there is nutritional status of children under five with ISPA where p-value= 0.001. There is a relationship between the existence of family members who smoke and nutritional status of children with ISPA in the working area of ​​Padongko Kec. barru district. new year 2019.